The Study of Water Allocation in Klong Yai Basin - Thanet Somboom; Kobkiat Pongput (Agriculture and Natural Resources, 2002)
Klong Yai Basin is sub-basin of east coast basin, and watershed area is 1,830 sq. kilometers in Rayong and Chonburi Province. The existing Dokrai reservoir and Nongpralai reservoir are main reservoirs and Klong Yai reservoir was suggested to support more water usage. A mathematical model, Acres Irrigation Support Package (AISP) was selected to simulate water allocation in Klong Yai basin at normally case (in 2000) and forecasting case (in 2009). AISP will calculate results from 1970 to 2000 to decide the operating rule curve and evaluation water delivery from external indicator was selected for water allocation in Klong Yai Basin. It was found that, the effective rainfall in dry seasons is more than wet season, at the same time the irrigation efficiency in dry season is 60 % and wet season is 55 %. Normally case in 2000, inflow rule and reservoir rule curve of Dokrai reservoir and Nongpralai reservoir will be used to operate the reservoirs in each year. In forecasting case in 2009, Reservoir rule curve of Klong Yai reservoir will be used to forecast water allocation in Klong Yai basin. The evaluation of water delivery found that, irrigation supply is 0.449 from industry supply, at the same time industry supply is 0.459 from reservoir capacity and irrigation supply is 1.697 from net irrigation demand which irrigation supply in dry season more than wet season.